Guinean landing surveys of Bentfin devil rays add insight into threatened elasmobranch catch - Shay Kashey; Framoudou Doumbouya; Betty Laglbauer; Isabel Ender; Daniel Fernando; Guy M. W. Stevens; Colin A. Simpfendorfer (Environmental Biology of Fishes, 2025)
Populations of many elasmobranchs have decreased globally, with over a third of species threatened with an elevated risk of extinction, largely due to fishing pressure. In West Africa, a general lack of species-specific catch data limits the ability to implement effective management, despite significant elasmobranch catch. The aim of this study was to (1) assess landings of mobulid rays, along with other elasmobranch species, recorded opportunistically in fisheries from Guinean waters, (2) provide information on the value and trade of these species, and (3) discuss management implications. Elasmobranchs were photographed and identified during market surveys over a ten-month period in 2014 and 2015, at four local Guinean fish markets: Bonfi, Boulbinet, Kassa, and Kamsar. A total of 1954 specimens, comprising 17 different elasmobranch species, were recorded across all markets. Of these species, 94% are assessed as threatened (vulnerable, endangered, critically endangered) and 6% are assessed as Near Threatened on the IUCN’s Red List of Threatened Species. The only mobulid species recorded was Mobula thurstoni , with significantly larger specimens recorded in Boulbinet, while in Bonfi fishing grounds overlapped with young-of-the-year specimens. When considering all elasmobranch landings, Bonfi and Boulbinet had similar species compositions, although when considering daily data, species composition tended to differ. Indicator Species Analysis indicated that Carcharhinus falciformis , Carcharhinus leucas , and Mustelus mustelus were top indicator species for Bonfi (with high specificity and fidelity), while Paragaleus pectoralis and Gymnura sereti were key indicator species for Boulbinet. Records of selling price at Bonfi were higher for various stingray species than larger shark species, suggesting meat as a primary driver of the fishery. This study adds insight into the species composition of elasmobranch catch in West Africa and highlights specific fishing sectors contributing to elasmobranch exploitation locally; information which is needed to understand the effects on regional stocks.

Quantifying the resistance of Australian wheat genotypes to Pratylenchus thornei based on a continuous metric from a factor analytic linear mixed model - Bethany Rognoni; Clayton R. Forknall; Steven Simpfendorfer; Richard Daniel; Luke Neale; Alison M. Kelly (Euphytica, 2024)
Genetic resistance to the parasitic root-lesion nematode, Pratylenchus thornei , is one of the main management strategies cereal growers can use to minimise the impact of nematodes on winter cereal cropping. Screening of genotypes in the presence of P. thornei populations must provide reliable resistance measures that are realised under field conditions. Adoption of the latest statistical methodologies can help to better differentiate between resistant and susceptible genotypes. In this study, post-harvest P. thornei population densities were measured from a collection of 17 field experiments, with varying starting P. thornei population densities, conducted between 2011 and 2018 in locations across the northern grain growing region of eastern Australia. The experiments primarily consisted of wheat genotypes. The post-harvest P. thornei population densities were analysed across multiple environments in a linear mixed model framework, with a factor analytic structure used to model genotype by environment (G $$×$$ × E) interaction effects exclusively for wheat genotypes. In general, genetic correlations between environments were found to be high, indicating limited G $$×$$ × E interaction for resistance to P. thornei . Post-processing of results using the factor analytic selection tools (FAST) method provided a measure of the overall performance for each wheat genotype, as well as a stability measure reflecting the consistency of the resistance status across environments. The FAST method quantified genotype resistance on a continuous scale, better reflecting the nature of genetic resistance based on a quantitative variable such as nematode population density, and provided a statistically robust and informative means of aiding selection decisions for resistance to P. thornei .

“Killer Joules”: spores of Bipolaris sorokiniana and fusarium species are susceptible to microwave radiation - Toni Petronaitis; Clayton Forknall; Graham Brodie; Steven Simpfendorfer; David Backhouse (Australasian Plant Pathology, 2022)
Cereal production in Australia is severely impacted by diseases such as Fusarium crown rot (caused predominantly by Fusarium pseudograminearum ) and common root rot (caused by Bipolaris sorokiniana ). These diseases are particularly difficult to manage because inoculum can survive at least three years within cereal stubble, or four years in soil in the case of B. sorokiniana . Microwave radiation may be able to reduce or eliminate inoculum within stubble and soil. Several cereal pathogens have been previously shown to be susceptible to microwave radiation, but the energy requirements to achieve a significant decrease in pathogen populations were not defined. Laboratory based microwave dose-response experiments on conidia of B. sorokiniana and macroconidia of F. pseudograminearum and F. cerealis revealed that all three pathogens are susceptible to microwave radiation, with lethal dose (LD) thresholds estimated for each pathogen. Bipolaris sorokiniana conidia required 103.8 Jg − 1 and 236.6 Jg − 1 of microwave radiation energy for LD50 and LD99, respectively, whilst F. pseudograminearum required 78.4 Jg − 1 and 300.8 Jg − 1 and F. cerealis required 95.3 Jg − 1 and 152.7 Jg − 1 for LD50 and LD99, respectively. These results were derived from experiments whereby samples were microwaved for up to 10 s using a domestic 1100 W microwave oven. These timing and energy requirements serve as a starting point to define requirements for further development of microwave radiation treatments under field conditions.

Stubble trouble! Moisture, pathogen fitness and cereal type drive colonisation of cereal stubble by three fungal pathogens - Toni Petronaitis; Clayton Forknall; Steven Simpfendorfer; David Backhouse; Richard Flavel (Australasian Plant Pathology, 2022)
Stubble-borne cereal diseases are a major constraint to production in Australia, with associated costs rising as a result of increased adoption of conservation agriculture systems. The fungal pathogens that cause these diseases can saprotrophically colonise retained cereal residues, which may further increase inoculum levels post-harvest. Hence, saprotrophic colonisation by the stubble-borne fungal pathogens Fusarium pseudograminearum , Pyrenophora tritici-repentis and Bipolaris sorokiniana were compared under a range of moisture conditions for stubble of six cereal varieties (two bread wheat, two barley, one durum wheat and one oat). Sterile cereal stubble was inoculated separately with two isolates of each pathogen and placed, standing, under constant relative humidity conditions (90, 92.5, 95, 97.5 and 100%) for 7 days at 25 °C. Stubble was then cultured in increments of 1 cm to determine the percentage colonisation height of each tiller. Fusarium pseudograminearum colonised farther within tillers, leaving a greater proportion of the standing stubble colonised compared with B. sorokiniana and P. tritici-repentis , suggesting F. pseudograminearum has higher saprotrophic fitness. Saprotrophic colonisation also increased with increasing relative humidity for all pathogens and varied by cereal type. Disease management strategies, such as reduced cereal harvest height, may limit saprotrophic colonisation and improve stubble-borne disease management in conservation agriculture systems.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Microwave radiation reduces survival of Fusarium pseudograminearum in durum wheat stubble - Toni Petronaitis; Clayton Forknall; Steven Simpfendorfer (Australasian Plant Pathology, 2018)

Movements of juvenile endangered smalltooth sawfish, Pristis pectinata, in an estuarine river system: use of non-main-stem river habitats and lagged responses to freshwater inflow-related changes - Gregg R. Poulakis; Philip W. Stevens; Amy A. Timmers; Christopher J. Stafford; Colin A. Simpfendorfer (Environmental Biology of Fishes, 2013)

Passage through alternative hosts changes the fitness of Fusarium graminearum and Fusarium pseudograminearum - Olufemi A. Akinsanmi; Sukumar Chakraborty; David Backhouse; Steven Simpfendorfer (Environmental Microbiology, 2007)
Summary Species of the necrotrophic fungal pathogen Fusarium that cause head blight and crown rot of cereals including wheat also infect a number of alternative host plants. This raises the prospect of more damaging pathogen strains originating and persisting as highly successful saprophytes on hosts other than wheat. The immediate impact on pathogenic (aggressiveness) and saprophytic (growth rate and fecundity) behaviour of six isolates with low, moderate or high initial aggressiveness was examined in two species of Fusarium after their passage through 10 alternative plant hosts. One passage through alternative hosts significantly reduced the pathogenic fitness of most isolates, but this change was not associated with a concomitant change in their overall saprophytic behaviour. The overall weak association between aggressiveness, fecundity and growth rate both before and after passage through the alternative hosts indicate that pathogenic and saprophytic fitness traits may be independently controlled in both Fusarium species. Thus, there was no trade‐off between pathogenic and saprophytic fitness in these necrotrophic plant pathogens.